Who needs words? : a Christian communications handbook - Littledale, Richard (Edinburgh: Saint Andrew Press, 2011)
Offers straightforward and practical help for those who wish to spread the Christian message in an effective, relevant and engaging way. This book presents a step-by-step method to enable you to improve the various ways in which you go about communicating. It provides constructive advice that can be applied in various situations.
Keywords: Communication -- Religious aspects -- Christianity